2018
DOI: 10.1002/etc.4088
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of 6 neonicotinoid insecticides to freshwater invertebrates

Abstract: Neonicotinoids are a group of insecticides commonly used in agriculture. Due to their high water solubility, neonicotinoids can be transported to surface waters and have the potential to be toxic to aquatic life. The present study assessed and compared the acute (48- or 96-h) toxicity of 6 neonicotinoids (acetamiprid, clothianidin, dinotefuran, imidacloprid, thiacloprid, and thiamethoxam) to 21 laboratory-cultured and field-collected aquatic invertebrates spanning 10 aquatic arthropod orders. Test conditions m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
78
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 40 publications
(73 reference statements)
10
78
1
1
Order By: Relevance
“…For example, Pochini and Hoverman () found that prior Ranavirus infection increased pesticide toxicity in wood frogs, specifically reducing the lethal concentration of thiamethoxam by 55% (from ~2.2 to ~1 mg/L). Finally, neonicotinoids could have indirect effects on amphibians by reducing prey abundance because insects have been found to be directly affected at much lower concentrations and well within the concentration range tested in the present study (Bartlett et al ; Raby et al ); this is similar to concerns for aerial insectivores, such as tree swallows (Gibbons et al ). Although the effects of individual neonicotinoids in controlled laboratory environments have provided important insights on their aquatic toxicology, interactive effects between chemical contamination and additional stressors such as predation or parasitism could provide a more comprehensive understanding of the risks of neonicotinoids in whole ecosystems (Marcogliese and Pietrock ).…”
Section: Discussionsupporting
confidence: 82%
“…For example, Pochini and Hoverman () found that prior Ranavirus infection increased pesticide toxicity in wood frogs, specifically reducing the lethal concentration of thiamethoxam by 55% (from ~2.2 to ~1 mg/L). Finally, neonicotinoids could have indirect effects on amphibians by reducing prey abundance because insects have been found to be directly affected at much lower concentrations and well within the concentration range tested in the present study (Bartlett et al ; Raby et al ); this is similar to concerns for aerial insectivores, such as tree swallows (Gibbons et al ). Although the effects of individual neonicotinoids in controlled laboratory environments have provided important insights on their aquatic toxicology, interactive effects between chemical contamination and additional stressors such as predation or parasitism could provide a more comprehensive understanding of the risks of neonicotinoids in whole ecosystems (Marcogliese and Pietrock ).…”
Section: Discussionsupporting
confidence: 82%
“…Dinotefuran and thiamethoxam showed the least potency, with EC50s for emergence of >8 µg L −1 for C. dilutus and >2 µg L −1 for N. triangulifer . This ranking follows both our assessment of chronic toxicity for the cladoceran Ceriodaphnia dubia (Raby et al, unpublished manuscript), acute toxicity for aquatic invertebrates (Raby et al ), and the ranking expressed in other studies. For example, Morrissey et al () summarized acute toxicity to aquatic insects for 6 neonicotinoids, and ranked thiacloprid and clothianidin highest, and dinotefuran and thiamethoxam lowest.…”
Section: Discussionmentioning
confidence: 64%
“…Neonicotinoids are designed to bind to the nicotinic acetylcholine receptors found in insect pests, causing a constant nerve stimulation that leads to changes in behavior and eventually death (Matsuda et al ; Morrissey et al ). Insects have been found to be among the most sensitive to neonicotinoids, and crustaceans the least (Morrissey et al ; Raby et al ). Previous work in our laboratory found that Chironomus dilutus (Insecta: Diptera) and Neocloeon triangulifer (Insecta: Ephemeroptera) were the most sensitive species in acute water‐only tests with 6 neonicotinoids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations